Організація науково-методичної діяльності бібліотеки ВНЗ - Боднар, Олена; Шишка, Олександр (Видавництво Львівської політехніки, 2012)
System of methodical management of libraries was reviewed at example of Scientific and Technical Library of the National University "Lviv Polytechnic". Also it was described the main principles and priorities of teaching services, described the main changes in the methods department.
Keywords: бібліотека; науково-методична робота; методична ообота у бібліотеці; управління; НТБ